2014
DOI: 10.1007/s00441-014-1933-6
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-induced vascular dynamics in the hippocampus of adult mouse brain

Abstract: New neurons are continuously added to hippocampal circuitry involved with spatial learning and memory throughout life. These new neurons originate from neural stem/progenitor cells (NSPCs) in the subgranular zone (SGZ) of the dentate gyrus (DG). Recent studies indicate that vascular reconstruction is closely connected with neurogenesis, but little is known about its mechanism. We have examined vascular reconstruction in the hippocampus of adult mouse brain after the administration of the antidepressant fluoxet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…13,14 In brief, cultured cells plated on poly-d-lysine-coated coverslips were fixed with 4% paraformaldehyde in 0.1 M phosphate-buffered saline (PBS) (pH 7.4) for 10 minutes. After permeabilization with 0.3% Triton X-100 in PBS (PBST), cells were blocked with 5% normal horse serum in PBST and incubated with Alexa Fluor-546-conjugated phalloidin and the following primary antibodies: mouse anti-collagen I (1:100, Abcam), rabbit anti-collagen IV (1:100, Progen), guinea pig anti-laminin (1:200, gift from Dr. Miyata), 22 mouse anti-Tuj1 (1:200, Covance), or rabbit anti-glial fibrillary acidic protein (GFAP; 1:1000, Abcam). They were further incubated with species-specific secondary antibodies conjugated with Alexa Fluor-488 (1:1000, Thermo Fisher) or CF-555 (1:1000, Biotium).…”
Section: Immunostainingmentioning
confidence: 99%
“…13,14 In brief, cultured cells plated on poly-d-lysine-coated coverslips were fixed with 4% paraformaldehyde in 0.1 M phosphate-buffered saline (PBS) (pH 7.4) for 10 minutes. After permeabilization with 0.3% Triton X-100 in PBS (PBST), cells were blocked with 5% normal horse serum in PBST and incubated with Alexa Fluor-546-conjugated phalloidin and the following primary antibodies: mouse anti-collagen I (1:100, Abcam), rabbit anti-collagen IV (1:100, Progen), guinea pig anti-laminin (1:200, gift from Dr. Miyata), 22 mouse anti-Tuj1 (1:200, Covance), or rabbit anti-glial fibrillary acidic protein (GFAP; 1:1000, Abcam). They were further incubated with species-specific secondary antibodies conjugated with Alexa Fluor-488 (1:1000, Thermo Fisher) or CF-555 (1:1000, Biotium).…”
Section: Immunostainingmentioning
confidence: 99%
“…The perivascular structures of the NH ( 47 – 50 ) and ME ( 51 ) largely differ from those generally observed in the brain because they have a wide perivascular space between the inner and outer BMs. Therefore, the profile of the outer BM or vascular surface in the NH [( 40 ); Figure 2 A] and ME [( 42 ); Figure 2 B] is more complex or uneven than that of the general BBB-containing brain vasculature [( 52 ); Figure 2 C]. This irregularity in the vascular surface is primarily due to the complex cellular processes of pericytes that function as vascular mural cells surrounding ECs [( 23 ); Figure 2 D].…”
Section: Significance Of the Perivascular Space In Neurosecretionmentioning
confidence: 99%
“…A previous study reported that the overexpression of VEGF-A significantly increased angiogenesis and neurogenesis in the adult hippocampus (Udo et al, 2008 ). Electroconvulsive seizures and antidepressants, which are proven therapeutics in the treatment of several depressive diseases, increased vascular density in the DG of adult rodents and humans (Newton et al, 2006 ; Mannari et al, 2014 ). NSCs have a perivascular niche that intimately associates with endothelial cells, possibly via VEGF and BDNF signaling, in the SGZ and SVZ of adult mammalian brains (Goldman and Chen, 2011 ).…”
Section: Angiogenesismentioning
confidence: 99%